Policy emergency and policy convergence: the case of 'scientific-bureaucratic medicine' in the United States and United Kingdom - Harrison, Stephen; Wood, Bruce; Moran, Michael (2002)
This article examines how the rather similar approaches to the management of medical care (which here we term `scientific-bureaucratic medicine') emerged within the public-policy agendas of both the United Kingdom and United States during the 1990s. In particular, we address the theoretical puzzle of how explanations of policy emergence in single countries can be reconciled with policy convergence between two countries. - Reproduced.
Keywords: Health services - Grreat Britain; Health services - United States; Health services